Commercializing smallholder value chains for goats in Mozambique: A system dynamics approach - Hamza, K.H.; Rich, Karl M.; Baker, A.D.; Hendrickx, Saskia C.J. (2014)
Goat producers in Inhassoro follow traditional management practices that lead to low supply of low quality goats. This has negative impacts on profitability, and on market access. Traders who buy in the Inhassoro locality buy only small volumes, and buyers from external markets are unaware of potential market supply in Inhassoro. This interaction of production constraints and limited information flows in the value chain was addressed using a system dynamics model for various commercialization scenarios. Simulation results show that improving goat production and animal health practices alone without concomitant improvements in market access have negative impacts on the financial performance of producers and no impact on other value chain actors. However, interventions that both improve market access and animal health have significant positive impacts on the financial performance of all value chain actors. The model’s explicit treatment of herd dynamics contribute significantly to these conclusions, particularly the lagged production response inherent in livestock breeding systems.